Kualitas bacaan cerminan kualitas diri: Hubungan antara kualitas bacaan dan kepercayaan diri individu dalam pembelajaran - Nazilah, Nishfi Rohmatun (Maliki Interdisciplinary Journal, 2024)
This research addresses the relationship between reading quality and individual confidence in the context of learning. Reading quality refers to the comprehension, analysis and interpretation of the text read, while individual self-confidence relates to a person's belief in his or her academic ability and competence in learning. Good reading quality can improve an individual's understanding of the subject matter, thus encouraging motivation for further learning. Individuals who are able to understand the text well tend to feel more confident in participating in class discussions and expressing opinions. Conversely, individuals with high self-confidence tend to be more proactive in doing reading activities, which in turn can improve the quality of their reading. By improving the quality of reading, individuals can develop critical and analytical thinking skills, which contribute to increased self-confidence. In addition, a supportive learning environment and access to quality reading materials also play an important role in building students' self-confidence. This research emphasizes the importance of integrating reading quality and self-confidence in learning, and the need for educational strategies that facilitate the development of both. By paying attention to this relationship, educators can create more effective learning experiences, increase student motivation and promote better academic achievement.